Mean amplitudes of vibration of some octahedral MF6 - Anions - Barán, Enrique José (2003)
The mean amplitudes of vibration of the hexafluoroanions of the groups 5 and 15 of the Periodic System have been calculated from known spectroscopic data between 0 and 1000 K. Bond peculiarities of these compounds are discussed, and some comparisons with related species are made.